Difficult path to the diagnosis of chromomycosis - Tatyana V. Melnikova; Natalya Yu. Burtseva; Tatyana A. Cheboksarova; Evgeny V. Sokolovskiy (State Scientific Center of Dermatovenereology and Cosmetology, 2024)
Chromomycosis is a slowly occurring mycosis of subcutaneous adipose tissue and skin. Most often, cases of the disease are recorded in countries with a tropical and subtropical climate. In the Russian Federation, the disease occurs sporadically. Very rarely (2 cases out of 100) malignant transformation into squamous cell carcinoma occurs. The article presents a clinical case of chromomycosis. A description is given of a patient in whom squamous cell carcinoma was detected at the onset of the disease, which was the reason for treatment by oncologists. Six months later, the patient had a relapse in the area of the postoperative scar and a focus in the area of the right hand. Repeated biopsy with histological examination made it possible to establish the correct diagnosis. Interest in the above clinical case was caused by the detection of chromomycosis in a resident of the city of Saint Petersburg, who was not in endemic areas, was not engaged in agricultural work, and denied the primary injury. Our patient experienced a rapid malignancy of the focus, after surgical treatment, a recurrence of deep mycosis occurred. A good effect was obtained from systemic antimycotic therapy.